Protecting right to privacy in Jordan in light of the COVID-19 pandemic: restrictions and guarantees - Shatha Ahmad Al-Assaf (Cogent Social Sciences)
This research highlights the legal guarantees offered by the Jordanian Constitution and Defense Law to protect the right to privacy after the enactment of the Defense Law because of the coronavirus 2019 (COVID-19) pandemic. It also aims to examine the Jordanian Constitution and Defense Law to understand its extent of compliance with standards outlined in international conventions on human rights. Moreover, the research explores the Defense Orders issued in Jordan to counter the COVID-19 pandemic and protect the right to privacy. The research adopts analytic and comparative methods. The most significant results denote the challenges encountered by Jordan due to the COVID-19 pandemic, revealing the failure of the legal system to protect the right to privacy and offer sufficient protection for such rights under exceptional circumstances. This drawback becomes particularly apparent when it comes to regulating restrictions that may be imposed on the rights and freedoms through the Defense Orders, according to the Defense Law, which is regulated by the Jordanian Constitution. Therefore, this research concludes that the Jordanian Constitution and Defense Law should be amended to comply with the standards of international conventions.